« Transition », vraiment? Clarifier les concepts pour nourrir l’éducation - Mathieu PAYN; Lionel ALVAREZ (Tic & Société)
This work proposes a realistic conceptualization of (1) the digitalization of society and (2) overcoming planetary boundaries to (3) put forward reasoned approaches to education with/about the digital, from discourse analysis to prospective proposals. First, using a multidisciplinary approach, the authors demystify the imperious discourses around digital technology and its ecological impact. Then, they present projects with low ecological impact and innovative pedagogical content based on solid computational knowledge.